Disrupting Legacies of Trauma: Interdisciplinary Interventions for Health and Human Rights - Joan Simalchik (Harvard FXB Center for Health and Human Rights, 2020)
The devastation caused by war and atrocity extends beyond the battlefield and creates conditions with severe public health consequences in affected societies. The infliction of socially organized mass violence and the suppression of reporting of harms has an impact on multiple levels: the individual, the familial, and the social. Ignacio Martín Baró, a Jesuit priest and social psychologist, explored the impact of psychosocial trauma while living and dying in the 1980-1992 Salvadoran civil war. His depiction of the multilevel impact of atrocity provides insight into the connection between health and human rights. This article discusses how his analysis of the constituent parts of psychosocial trauma continues to hold relevance for understanding the legacy of historical events and points to possibilities for mitigating health harm in various contemporary contexts.